2005
DOI: 10.1111/j.1471-4159.2005.03451.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of sphingosine kinase 1 as a mediator of neurotrophin‐3 action in oligodendrocyte progenitors

Abstract: We had found previously that neurotrophin-3 (NT-3) is a potent stimulator of cAMP-response element binding protein (CREB) phosphorylation in cultured oligodendrocyte progenitors. Here, we show that CREB phosphorylation in these cells is also highly stimulated by sphingosine-1-phosphate (S1P), a sphingolipid metabolite that is known to be a potent mediator of numerous biological processes. Moreover, CREB phosphorylation in response to NT-3 involves sphingosine kinase 1 (SphK1), the enzyme that synthesizes S1P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 86 publications
(202 reference statements)
2
58
2
Order By: Relevance
“…Although the neurotrophic factors NT-3, BDNF, and GDNF are reported to be induced or to interact with FTY720 during OPC differentiation, 47,56 no significant difference was observed in our study, indicating that FTY720-induced NSC differentiation is not through induction by these neurotrophic factors. We then focus on the S1P receptors, the designated interaction partners of phosphorylated FTY720, and their downstream signaling during NSC differentiation.…”
Section: Discussioncontrasting
confidence: 47%
“…Although the neurotrophic factors NT-3, BDNF, and GDNF are reported to be induced or to interact with FTY720 during OPC differentiation, 47,56 no significant difference was observed in our study, indicating that FTY720-induced NSC differentiation is not through induction by these neurotrophic factors. We then focus on the S1P receptors, the designated interaction partners of phosphorylated FTY720, and their downstream signaling during NSC differentiation.…”
Section: Discussioncontrasting
confidence: 47%
“…[3] In addition to playing a role in the immune system, all S1P receptors except S1P4 are also found differentially expressed in the central nervous system [4] and on various tumor cell types. [5,6] Although the precise regulation of these receptors by locally released S1P remains unclear, S1P receptors are thought to play a role in such events as astrocyte migration, [7] oligodendrocyte differentiation, and cell survival [8,9] and neurogenesis. [10,11] To assess the relevance of individual S1P receptor subtypes for the activity of FTY720-P, selective agonists are required.…”
mentioning
confidence: 99%
“…Samples (15 l) were subjected to SDS-polyacrylamide gel electrophoresis in 12% acrylamide, and the proteins were electrotransferred to nitrocellulose. The membranes were then subjected to immunoblot analysis as previously reported (Saini et al, 2005), with minor modifications. Nonspecific antibody binding to the blots was blocked by incubation in 10 mM Na 2 HPO 4 , 2.7 mM KCl, and 137 mM NaCl, pH 7.4, (PBS) containing 3% nonfat dry milk and 0.05% Tween 20 (blocking solution) for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Because of its similarity to S1P, FTY720-P is able to bind to all of the high-affinity S1P receptors except S1P 2 (Brinkmann and Lynch, 2002). We have previously found that S1P signaling plays a crucial role as a mediator in the stimulation of OLG progenitor survival by neurotrophin-3 (NT-3) (Saini et al, 2005). This observation led us to hypothesize that FTY720 could, like S1P, have a direct effect on the OLG progenitors.…”
mentioning
confidence: 99%